Lucknow's imambaras are Hindu palaces - Oak, P. N. (Purushottam Nagesh), 1917-2007 (Jaico Pub. House, 1976)
Presentation of the thesis that the Shiite religious buildings (imambaras) of Lucknow were originally ancient Hindu palaces.